Is There Still a Need for Universities in The AI Era? Reading Fathul Wahid's Arguments from the Perspective of Islamic Education - Rizky Firnanda; Sri Haningsih; Irfan Maulana Adnan; M. Naseh Ulwan (JURNAL ILMIAH DETUBUYA, 2026)
In the era of artificial intelligence (AI), the existence of universities as institutions of higher education has become a pressing question, especially regarding their role in shaping students' character, morals, and critical thinking within the context of Islamic education. This article analyzes the relevance of universities amid the advancement of AI, drawing on Fathul Wahid's arguments regarding the preservation of academic functions and religious values. The methods used are a literature review and a conceptual analysis of Wahid's works, with a focus on how universities can serve as forums for integrating science, ethics, and spiritual values in Islamic higher education. The findings show that, even though AI offers easy access to information and supports innovation in the learning process, universities still play an irreplaceable strategic role, namely shaping character, critical thinking, and a comprehensive understanding of religious values. The conclusion of this article emphasizes that universities remain relevant in the AI era, and their. The main contribution is to emphasize the importance of integrating knowledge and religious values as the foundation of Islamic higher education, thereby producing a generation that is intelligent, moral, and adaptable to technological developments.